2002
DOI: 10.1034/j.1399-6576.2002.460808.x
|View full text |Cite
|
Sign up to set email alerts
|

Extubation after breathing trials with automatic tube compensation, T‐tube, or pressure support ventilation

Abstract: After the inclusion of 90 patients (30 per group) we did not observe significant differences between the modes. Twelve patients failed the initial weaning trial. However, half of the patients who appeared to fail the spontaneous breathing trial on the T-tube, PSV, or both, were successfully extubated after a succeeding trial with ATC. Extubation was thus withheld from four and three of these patients while breathing with PSV or the T-tube, respectively, but to any patient breathing with ATC. It seems that ATC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 28 publications
4
81
0
11
Order By: Relevance
“…30,34 Automatic tube compensation, a ventilator setting that makes up for the pressure drop across the ETT, is comparable to low-level PSV or a T-piece. 35 The duration of an SBT should be at least 30 min 30 ; no benefit is gained from prolonging the duration of an SBT to 120 min. 36,37 The rate of weaning failure after an initial SBT has been reported to be 25-40%.…”
Section: Weaning From Mechanical Ventilationmentioning
confidence: 99%
“…30,34 Automatic tube compensation, a ventilator setting that makes up for the pressure drop across the ETT, is comparable to low-level PSV or a T-piece. 35 The duration of an SBT should be at least 30 min 30 ; no benefit is gained from prolonging the duration of an SBT to 120 min. 36,37 The rate of weaning failure after an initial SBT has been reported to be 25-40%.…”
Section: Weaning From Mechanical Ventilationmentioning
confidence: 99%
“…Similar data were recorded by Ezingeard et al (Ezingeard et al, 2006). However, Haberthur et al (2002) found no significant differences among the 3 protocols.…”
Section: Conventional Ventilation Modesmentioning
confidence: 55%
“…During spontaneous breathing, ATC compensates for the flow-dependent ⌬P ETT on the basis of the calculated pressure, not on the actual pressure measured at the distal end of the ETT. 7 The ⌬P ETT can be approximated with the following equation 8 :…”
Section: Discussionmentioning
confidence: 99%
“…17 In ATC mode, a ventilator measures flow and calculates the pressure required to overcome the flow-dependent resistive work load of the ETT. [5][6][7][8][9] The ATC calculations/algorithms are assuming a new, clean, and not deformed tube; because the calculation is based on the inner diameter and length of the ETT as well as on the measured flow, changes in the inner diameter of the ETT can hamper the accuracy of this calculation. Decrease in inner diameter induces increase in resistance, thus pressure drop is underestimated, and compensation is insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation